The Constitution of the Republic of the Philippines explained - Nolledo, Jose N. (Mandaluyong City, Philippines : National Book Store, 2002)
PREAMBLE We, the sovereign Filipino people, imploring the aid of Almighty God, in order to build a just and humane society and establish a Government that shall embody our ideals and aspirations, promote the common good, conserve and develop our patrimony, and secure to ourselves and our posterity the blessings of independence and democracy under the rule of law and a regime of truth, justice, freedom, love, equality, and peace, do ordain and promulgate this Constitution.
Preamble -- Article I- National territory -- Article II- Declaration of Principles and State Policies -- Article III- Bill of Rights -- Article IV- Citizenship -- Article V- Suffrage -- Article VI- Legislative Department -- Article VIII- Judicial Department -- Article IX- Constitutional Commissions -- Article X- Local Government -- Article XI- Accountability of public offcicers -- Article XII- National economy and Patrimony -- Article XIV- Education, Science and Technology, Arts, Culture and Sports -- Article XV- The Family -- Article XVI- General Provisions -- Article XVII- Amendments of Revisions -- Article XVIII- Transitory of Provisions -- Appendix, Members of the 1986 Constitutional Commission.
Keywords: PHILIPPINE -- CONSTITUTION